Motives for Minors Working as Farm Workers - Firdaus W. Suhaeb; Ernawati S. Kaseng (Journal of Social Science and Economics (JOSSE), 2024)
This study aims to understand the motives of underage children working as farm laborers in Pencong Village, Biringbulu District, Gowa Regency, and its impact on their education and health. The study used a qualitative approach with a case study type, involving in-depth interviews with children, parents, and community leaders. In this study, the data collection techniques used are in the form of observation, interviews and documentation. The data collected was then analyzed with a quantitative descriptive approach through three main steps, namely data reduction, data presentation, and conclusion drawn., The results of the study indicate that the main motives for children to work are influenced by economic, social, and cultural factors. Family economic limitations are the dominant reason, while social norms and local traditions that support early work also play an important role. Farm labor work has a negative impact on children's education, causing absenteeism and low academic achievement. In addition, heavy physical work affects children's physical and mental health. This study concludes the need for social interventions, economic assistance, and more flexible education programs to reduce child labor in rural areas.